Algeria : 2010 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Algeria. (IMF Staff Country Reports; Country Report ;, 2011)
Despite the effects of the international crisis, real nonhydrocarbon GDP (NHGDP) growth in 2009 exceeded the average of 6 percent. Algeria's good economic performance supported by the authorities' prudent fiscal and monetary policies and the favorable external environment are welcomed. The authorities' policy to maintain the real effective exchange rate close to equilibrium, which is consistent with external stability, is encouraged. Containing government spending would contribute to reducing pressures for real exchange appreciation and potential Dutch disease effects.